Pengaruh Pertumbuhan Penjualan, Pertumbuhan Perusahaan, dan Ukuran Perusahaan Terhadap Nilai Perusahaan PT Ciputra Development Tbk Tahun 2013-2020 - hananing romadhoni (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2022)
The purpose of this study is to comprehend and explain the findings of the Pengaruh Pertumbuhan Penjualan, Pertumbuhan Perusahaan, and Ukuran Perusahaan With Regard to Nilai Perusahaan at PT Ciputra Development Tbk for the years 2013 to 2020. Utilizing quantitative methods as research methodology. All of PT Ciputra Development's keuangan plans for the years 2010 to 2022 as well as the plans for the years 2013 to 2020 as a whole. Data analysis employs linear regressive berganda analysis. Pertumbuhan penjualan secara parsial, according to the results of the study, bears a negative impact on the value of the company, whereas pertumbuhan perusahaan and ukuran perusahaan do not bear any negative impacts on the value of the company. There is a significant difference in the value of the company and its size when penjualan, business, and organizational structure are all taken into account simultaneously. It is necessary for businesses to conduct evaluations in order to increase their profitability. Investors may view this as a building block for developing persuasive arguments for the benefits of owning stock.